Dye-sensitized solar cells based on MK2 dye, PMMA-based quasi-solid electrolyte, and flexible CNT counter electrode. (December 2020) - Nguyen, Dang-Trang; Iwai, Toshiki; Taguchi, Kozo
Abstract: In this paper, a dye-sensitized solar cell based on organic MK2 dye, a quasi-solid electrolyte, and a flexible counter electrode was investigated. Two types of TiO2 nanoparticles with different sizes were used to make the photoanode with a bi-layer structure. The quasi-solid electrolyte was made based on polymethylmethacrylate (PMMA) and iodide/triiodide couple. The counter electrode was fabricated by electrophoresis deposition of carbon nanotube (CNT) mixed with diallyl dimethylammonium chloride (PDDA) on a flexible stainless-steel mesh. A cellulose separator was used to improve the stability of the solar cell. A simple and low-cost sealing method using polypropylene-based tape has been proposed and used for conducting the stability test. The maximum conversion efficiency of 2.5% (under simulated AM 1.5) was obtained with the fabricated quasi-solid dye-sensitized solar cells.